Romania : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Romania during 1990-97. Reforms have been relatively slow since the beginning of the transition process. Except for a brief and inconsequential interlude in 1993, comprehensive programs for privatization and for restructuring or liquidation of loss-making enterprises were not launched until 1995. These programs have done little to improve governance so far. As of end-1996, the economy was still largely characterized by state ownership and control; by fixed prices and quantitative constraints; and by ailing enterprises and subsidization of losses.